Embryonic Development of Grasshopper Populations Along Latitudinal Gradients Reveal Differential Thermoaccumulation for Adaptation to Climate Warming - Hao, Shuguang; Liu, Chunxiang; Ma, Chuan; Guo, Wei; Kang, Le (Frontiers in Ecology and Evolution, 2021)
Climate warming has a remarkable effect on the distribution, phenology, and development of insects. Although the embryonic development and phenology of non-diapause grasshopper species are more susceptible to warming than those of diapause species, the responses of developmental traits in conspecifically different populations to climate warming remain unknown. Here, we compared the mtDNA sequences and embryonic development of eight populations of grasshopper species (Chorthippus dubius) in field-based manipulated warming and laboratory experiments. The mtDNA sequences showed a significant genetic differentiation of the southernmost population from the other seven populations on the Mongolian Plateau. The embryonic development of the southernmost population was significantly slower than those of the northern populations at the same incubation temperatures. Interestingly, laboratory experiments showed that a significant difference exists in the effective accumulated degree days (EADD) but not in the lower development threshold temperatures (LDTT) among the different populations. The high-latitude populations required less EADD than the low-latitude populations. The warming treatments significantly accelerated the embryonic development in the field and decreased duration from embryos to hatchlings of all eight populations in the incubation. In addition, warming treatments in field significantly increased EADD requirement per stage in the incubation. Linear regression model confirmed that the embryonic development characteristics of eight populations were correlated with the annual mean temperature and total precipitation of embryonic development duration. The results indicated that grasshopper species have evolved a strategy of adjusting their EADD but not their LDTT to adapt to temperature changes. The variations in the EADD among the different populations enabled the grasshopper eggs to buffer the influences of higher temperatures on development and preserve their univoltine nature in temperate regions while encountering warmer climatic conditions. Thus, the findings of this study is valuable for our understanding species variation and evolution, and as such has direct implication for modeling biological response to climate warming.